Protagonismo juvenil por meio de monitoria na escola com o uso das novas tecnologias de informação e comunicação no ensino médio - Silva, Leandro Rodrigues da (2009)
This research is a case study carried out along with twenty monitor students of a collaborative learning project who helped the college researcher/teacher of mathematics and information technology at private and public schools of Sao Paulo state using SAI (Information Technology Room) rooms during one year. The research wants to demonstrate: 1. the juvenile participative action strength through collaborative learning assisted by the information and communication technology tools; 2. that the mathematics teaching and learning process is favored when there is an effective student involvement. It claims that the learning process can become expressive by using the TIC (Information and Communication Technologies) through cognitive tools within learning environments. It shows that the interpersonal relationship among monitor students, students and teachers are enhanced when there is dialog and mutual respect. It also contributes to the social and digital inclusion, making the learning process more joyful and allowing the youth to be the protagonist of their own educational process